Potential of Strawberry Fruit (Fragaria Vesca L), Coffee (Coffea), and Honey (Honeybee) as Facial Mask to Smooth the Face - Annisa Luthfiana Kusuma Ningrum; Nurmahni Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Facial masks are skin care products used on the face, one of the benefits of facial masks is that the face looks more moisturized. This study aims to determine how the potential of strawberry fruit (Fragaria Vesca L.), coffee (Coffea), and honey (Honeybee) to smooth the face. The research method used is experimental research method. The experimental method is a study conducted to find the effect of something that is done intentionally by the researcher. The results of the analysis of the face mask are the color of the face mask has a percentage of S = 100%. The aroma of the face mask has a percentage of S = 100%. The texture of the face mask has a percentage of S = 50%, N = 12.5%, KS = 12.5%, and TS = 25%. The stickiness of the face mask has a percentage of S = 62.5%, N = 12.5%, KS = 05, and TS = 25%. This face mask is suitable for use on the skin because it can smooth our facial skin.